Vertical Profile of Wind Diurnal Cycle in the Surface Boundary Layer over the Coast of Cotonou, Benin, under a Convective Atmosphere - Donnou, Hagninou E. V.; Akpo, B. Aristide; KOUCHADE, ADÉYÈMI CLÉMENT; KOUNOUHEWA, Basile; Houngue, Guy H.; Nonfodji, Gbènoukpo F.; DJOSSOU, Julien (My University, 2019)
)e characteristics of the wind vertical profile over the coast of Cotonou during wind convective diurnal cycle were explored in this study. Wind data at 10mabove the ground and the radiosonde data in the lower 60m of the surface boundary layer were used over the period from January 2013 to December 2016. Based on Monin–Obukhov theory, the logarithmic and power laws have allowed characterizing the wind profile.)eerror estimators of the Root Mean Square Error (RMSE) and the Mean Absolute Error (MAE) were, respectively, evaluated at 0.025; 0.016 (RMSE; MAE) and 0.018; 0.015. At the site of Cotonou, the atmosphere is generally unstable from 09:00 to 18:00 MST and stable for the remainder of the time. the annual mean value of the wind shear coefficient is estimated at 0.20 and that of the ground surface roughness length and friction velocity are, respectively, of 0.007 m, 0.38m·s−1. A comparative study between the wind extrapolation models and the data was carried out in order to test their reliability on our study site. The result of this is that whatever the time of the year is, only the models proposed (best fitting equation) are always in good agreement with the data unlike the other models evaluated. Finally, from the models suitable for our site, the profile of wind convective diurnal cycle was obtained by extrapolation of the wind data measured at 10m from the ground. The average wind speed during this cycle is therefore evaluated to 8.07m·s−1 for August which is the windiest month and to 4.98m·s−1 for the least windy month (November) at 60m of the ground. Considering these results, we can so consider that the site of Cotonou coastal could be suitable for the installation of wind turbines.
Keywords: wind; Monin–Obukhov; cotonou